Niezwykłe sąsiedztwo. Uniwersytet Powszechny i Biblioteka Sejmu Śląskiego (PDF 2,06 MB) (Książnica Śląska, 2025)
On February 12, 1935, the Uniwersytet Powszechny began operating in the building of the Dom Oświatowy in Katowice. The articledescribes the genesis, history and activity of this extracurriculareducation institution, and at the same time reminds of the figuresof lecturers and students. The Uniwersytet Powszechny in Katowiceeducated adults, while enabling them to actively participate in thelocal cultural and social life. The text characterizes the relationship between the Uniwersytet Powszechny and the Biblioteka Sejmu Śląskiego and reminds of the first verse report of a visit to the libraryin February 1935, written by Fryderyk Oczadły, a student of the Uniwersytet Powszechny.